A pilot randomized controlled trial of time-intensive cognitive–behaviour therapy for postpartum obsessive–compulsive disorder: effects on maternal symptoms, mother–infant interactions and attachment. Issue 8 (31st January 2017) - Challacombe, F. L.; Salkovskis, P. M.; Woolgar, M.; Wilkinson, E. L.; Read, J.; Acheson, R.
Abstract : Background: There is increasing recognition that perinatal anxiety disorders are both common and potentially serious for mother and child. Obsessive–compulsive disorder (OCD) can be triggered or exacerbated in the postpartum period, with mothers reporting significant effects on parenting tasks. However, there is little evidence concerning their effective treatment or the impact of successful treatment on parenting. Method: A total of 34 mothers with OCD and a baby of 6 months old were randomized into either time-intensive cognitive–behaviour therapy (iCBT) or treatment as usual (TAU). iCBT took place after randomization at 6 months postpartum and was completed by 9 months. Maternal symptomatology, sensitivity in mother–infant interactions and parenting were assessed at baseline and reassessed at 12 months postpartum. At 12 months attachment was also assessed using Ainsworth's Strange Situation Procedure. A healthy control group of mothers and infants ( n = 37) underwent the same assessments as a benchmark. Results: iCBT was successful in ameliorating maternal symptoms of OCD (controlled effect size = 1.31–1.90). However, mother–infant interactions were unchanged by treatment and remained less sensitive in both OCD groups than a healthy control group. The distribution of attachment categories was similar across both clinical groups and healthy controls with approximately 72% classified as secure in each group. Conclusions: iCBT is an effective intervention for postpartum OCD. Sensitive parenting interactions are affected by the presence of postpartum OCD and this is not improved by successful treatment of OCD symptoms. However, the overall attachment bond appears to be unaffected. Longitudinal studies are needed to explore the impact of postpartum OCD as the child develops.